Design study of a HPGe detector array for β-decay investigation in laboratory ECR plasmas - Naselli, Eugenia; Santonocito, Domenico; Amaducci, Simone; Celona, Luigi; Galatà, Alessio; Goasduff, Alain; Mauro, Giorgio Sebastiano; Mazzaglia, Maria; Mishra, Bharat; Napoli, Daniel R.; Pidatella, Angelo; Torrisi, Giuseppe; et al. (Frontiers in Physics, 2022)
In the frame of the PANDORA project, a new experimental approach aims at measuring in-plasma beta-decays rate as a function of thermodynamical conditions of the environment, namely a laboratory magnetized plasma able to mimic some stellar-like conditions. The decay rates (expected to change dramatically as a function of the ion ionization state) will be measured as a function of the charge state distribution of the in-plasma ions, changing plasma conditions. The new experimental approach aim to correlate the plasma environment and the decay itself. This can be done by simultaneously identifying and discriminating - through an innovative multi-diagnostic system working synergically with a gamma-rays detection system - the photons emitted by the plasma and gamma-rays emitted after the isotope beta-decay. In this paper, the numerical simulations supporting the design of the gamma-rays detectors array, including a statistical significance study to check the feasibility of measuring the in-plasma decay rates, are presented. GEANT4 simulations were focused on the design of the array of gamma-ray detectors and investigating the total efficiency in terms of detectors type and their optimal displacement around the trap (including collimation systems and shielding). The simulations results showed that, due to technical limitation in the number of cones of view that can be created in the magnetic trap, the best compromise is to use 14 HPGe (70% of relative efficiency) detectors surrounding the magnetic trap. The HPGe detectors were chosen for their high resolution (0.2% @ 1MeV), since the harsh-environment (the background is represented by the intense plasma self-emission) strongly affects the signal-to-noise ratio. Once determined the total photopeak efficiency (0.1-0.2%), the sensitivity of the PANDORA experiment was checked in a "virtual experiment run", by exploring the measurability of isotopes decay rates (for the firsts physical cases of PANDORA: 176Lu, 134Cs, 94Nb). The preliminary results demonstrated the feasibility of the measurement in terms of signal-to-background ratio and significance that it is possible to reach. Results indicated that experimental runs durations should take several days to 3 months, depending on the isotope under investigation, thus shading new light on the role of weak interaction on the stellar nucleosynthesis.